Learning styles of fully residential schools students in Mathematics through the flipped classroom method: do gender factors cause different impacts? - A.Rahman Azlina, Mohd Zaid Norasykin, Aris Baharuddin, Mohamed Hasnah, Abdullah Zaleha (Universiti Pendidikan Sultan Idris, 2017)
Learning styles of fully residential schools students in Mathematics through the flipped classroom method: do gender factors cause different impacts? by A.Rahman Azlina, Mohd Zaid Norasykin, Aris Baharuddin, Mohamed Hasnah, Abdullah Zaleha,